2023
DOI: 10.1002/agt2.388
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the efficiency‐stability‐cost balanced organic solar cell based on a polymerized nonfused‐ring electron acceptor

Abstract: Organic solar cells (OSCs) have attracted extensive attention from both academia and industry in recent years due to their remarkable improvement in power conversion efficiency (PCE). However, the Golden Triangle (the balance of efficiency‐stability‐cost) required for large‐scale industrialization of OSCs still remains a great challenge. Here, a new nonfused‐ring electron acceptor (NFREA) BF and its polymerized counterpart PBF were designed and synthesized, and their photovoltaic performance, storage stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Subsequently, we conducted a comparison of the device stability of a polymer acceptor PBF with a small-molecule one BF (Figure 5d). 23 It was observed that PBF exhibited enhanced thermal stability, light-absorbing ability, and tighter π−π stacking when compared with BF. Thus, the PBF-based device delivered a remarkable PCE of 12.61%, marking a significant improvement over the PCE of 11.10% achieved by the BF counterpart.…”
Section: Polymerized Nfreas: a Balance Among Efficiency Stability And...mentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, we conducted a comparison of the device stability of a polymer acceptor PBF with a small-molecule one BF (Figure 5d). 23 It was observed that PBF exhibited enhanced thermal stability, light-absorbing ability, and tighter π−π stacking when compared with BF. Thus, the PBF-based device delivered a remarkable PCE of 12.61%, marking a significant improvement over the PCE of 11.10% achieved by the BF counterpart.…”
Section: Polymerized Nfreas: a Balance Among Efficiency Stability And...mentioning
confidence: 99%
“…Copyright 2022 Science China Press and Springer-Verlag GmbH Germany, part of Springer Nature. (e–h) Reproduced with permission from ref . Under a Creative Commons CC BY license.…”
Section: Polymerized Nfreas: a Balance Among Efficiency Stability And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stability stands as a pivotal criterion in the pursuit of OPVs . The efficiency degradation of OPVs encompasses multiple factors, including material degradation caused by water and oxygen, stability of the active layer morphology, and induced effects at the interface layers. Among them, the inherent stability of the acceptor has been identified as one of the key factors in device stability . Existing studies have indicated that the acceptor may undergo processes such as photo-oxidation and intramolecular ring closing under light exposure. , In our previous research, we proposed that photoinduced double bond isomerization could serve as a precursor step triggering these degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cyano-containing polymers are a large group of fascinating materials with unique mechanical, electrical, and coordination properties, which are widely applicable in fibrous materials, 1 electrical conductivity, 2 solar cells 3 and covalent organic frameworks. 4 Cyano-containing polymers are generally prepared by the direct polymerization of cyano-containing monomers through radical polymerization, 5,6 Suzuki coupling, 7 pressure-induced polymerization, 8,9 triple-bond-based polymerization, 10 and the hydro(solvo)thermal synthesis method.…”
Section: Introductionmentioning
confidence: 99%